2020
DOI: 10.3390/en13123187
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Geothermal Utilization in the Context of European Energy Policy—Implications and Limitations

Abstract: The European Union (EU) has made climate change mitigation a high priority though a policy framework called “Clean Energy for all Europeans “. The concept of primary energy for energy resources plays a critical role in how different energy technologies appear in the context of this policy. This study shows how the calculation methodologies of primary energy content and primary energy factors pose a possible negative implication on the future development of geothermal energy when comparing against EU’s key ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
5
11
0
Order By: Relevance
“…In 2015, updated targets from the 2020 package were released in the new 2030 climate and energy framework, “Clean energy for all Europeans.” Revision on the target, increased efficiency and renewable energy share, was made in 2018. In December 2019, a long term strategy to achieve “climate‐neutral” by 2050 was formulated in “The European Green deal” growth strategy for the EU 153 . This supportive legal framework has help in the encouraging growth of geothermal energy utilization across Europe and can be used as benchmark for other region 154 …”
Section: Government Policymentioning
confidence: 99%
“…In 2015, updated targets from the 2020 package were released in the new 2030 climate and energy framework, “Clean energy for all Europeans.” Revision on the target, increased efficiency and renewable energy share, was made in 2018. In December 2019, a long term strategy to achieve “climate‐neutral” by 2050 was formulated in “The European Green deal” growth strategy for the EU 153 . This supportive legal framework has help in the encouraging growth of geothermal energy utilization across Europe and can be used as benchmark for other region 154 …”
Section: Government Policymentioning
confidence: 99%
“…For the Hellisheidi CHP plant, the majority of the LCA studies reported in the literature have focused on a cradle-to-grave approach and the inventory (LCI) provided by Karlsdòttir et al [16,17]. In these works, secondary data based on an ecoinvent v3.4 database were considered, and the CML-IA baseline and the cumulative energy demand (CED) were selected as the evaluation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Karlsdottir et al [11] discussed the possibility of using different methods to calculate partitioning and allocation factors, to be later applied for evaluating the products generated in the geothermal CHP plant. Specifically, they applied the following approaches: no allocation, energy, exergy, economic, and alternative generation method, to divide the primary energy factor (PEF) and greenhouse gas (GHG) emissions between power and heat produced at the Hellisheidi geothermal power plant.…”
Section: Introductionmentioning
confidence: 99%